Parental phubbing and problematic smartphone use among adolescents: The mediating role of parental attachment - Liza Marini; Wiwin Hendriani; Primatia Yogi Wulandari; Vahid Norouzi Larsari (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2025)
In the post-pandemic era, a new challenge has emerged within families: the increasing tendency toward problematic smartphone use (PSU). Parents’ attention is often divided between digital interactions and their children, parents appear available but are mentally preoccupied with digital interactions, leaving them physically present but psychologically absent during shared moments—a phenomenon known as parental phubbing. This study examined how parental phubbing contributes to adolescents’ PSU and tested whether the quality of parental attachment mediates this relationship. Data were collected from 654 adolescents aged 12–18 years in Medan, Indonesia, using cluster sampling. Participants completed the Parental Phubbing Scale (PPS), the Inventory of Parent and Peer Attachment–Revised (IPPA-R), and the Smartphone Addiction Scale–Short Version (SAS-SV). Path analysis showed that parental phubbing directly predicted higher PSU levels (β = .270, p < .001) and indirectly influenced PSU through reduced parental attachment (β = .054, p < .001). The mediation model, confirmed by the Sobel test (z = 9.24, p < .001), indicated partial mediation. These findings highlight the need to foster secure parent–child relationships and promote mindful digital engagement among parents to reduce adolescents’ vulnerability to smartphone overuse in the evolving post-pandemic family environment.